2009
DOI: 10.2503/jjshs1.78.195
|View full text |Cite
|
Sign up to set email alerts
|

Potential Involvement of Cs1-MMP in the Arrest of Sex Organ Development during Sexual Expression in Cucumber (Cucumis sativus L.)

Abstract: Monoecious cucumber (Cucumis sativus L.) produces male and female flowers on the same plant. In the early bisexual stage, all flower buds contain primordia for both stamens and pistils and sexual differences are established by the selective arrest of sexual organ primordia. Recently, the Cs1-MMP gene was isolated from a cucumber cotyledon. Cs1-MMP encodes a putative matrix metalloproteinase (MMP) and is expressed at the boundary of senescence and programmed cell death (PCD) of the cotyledon. In animals, MMPs m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…MMPs are a major group of enzymes that degrade the extracellular cell matrix (ECM) and are thought to play an important role in pathological processes such as arthritis, cancer and fibrotic diseases in animals (Woessner, 1998). We previously showed strong Cs1-MMP expression in the ACASP in female flower buds at stage I-III and in the ACAPP in male flower buds at stage I-III of monoecious cucumber plants (Yamasaki and Manabe, 2009 indicate that PCD is involved in the arrest of stamen primordia in female flower buds of monoecious cucumber plants. Taken together with the results of the current study, it appears that cells under division, restrained growth, and death coexist in the ASP in female flower buds of monoecious cucumber plants.…”
Section: Resultsmentioning
confidence: 99%
“…MMPs are a major group of enzymes that degrade the extracellular cell matrix (ECM) and are thought to play an important role in pathological processes such as arthritis, cancer and fibrotic diseases in animals (Woessner, 1998). We previously showed strong Cs1-MMP expression in the ACASP in female flower buds at stage I-III and in the ACAPP in male flower buds at stage I-III of monoecious cucumber plants (Yamasaki and Manabe, 2009 indicate that PCD is involved in the arrest of stamen primordia in female flower buds of monoecious cucumber plants. Taken together with the results of the current study, it appears that cells under division, restrained growth, and death coexist in the ASP in female flower buds of monoecious cucumber plants.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of bisexual flowers, both pistils and stamens continue to develop. Recently, it was shown that the Cs1-MMP gene, which encodes putative matrix metalloproteinase (MMP), may play an important role in the programmed cell death-mediated arrest of sexual organ primordia in cucumber flowers (Yamasaki and Manabe, 2009); however, the precise mechanism of the arrest of sexual organ primordia is still not clear in cucumber plants. In addition, factors located downstream of ethylene signals in cucumber sex expression have yet to be clarified, even though F and M genes have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…In female flowers, the highest expression was observed in sepals and in the area of stamen primordial arrest. These results suggest that Cs1-MMP plays an important role in PCD-mediated arrest of sexual organs in flowers (Yamasaki and Kazuto 2009). Several techniques have been used to identify genes correlated with sex determination in cucumber; these include AFLP (Witkowicz et al 2003) as well as RAPD and subtraction (DSC) techniques (Przybecki et al 2003(Przybecki et al , 2004 performed on genomes of near-isogenic lines of different sex types.…”
Section: Genes Correlated With Floral Morphogenesismentioning
confidence: 99%
“…The authors speculate that CsSUP act as regulators that stimulate and suppress a CsAP3 transcription (Pan et al 2018). Yamasaki and Kazuto (2009) studied Cs1-MMP, which encodes a putative matrix metalloproteinase connected with PCD. In male cucumber flowers, the strongest expression was detected in sepals and in the area where pistil primordia were arrested.…”
Section: Genes Correlated With Floral Morphogenesismentioning
confidence: 99%